2004
DOI: 10.1029/2004gl021169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ocean transport through Drake Passage during the 1980s and 1990s, forced by changes in the Southern Annular Mode

Abstract: We present the first direct evidence that interannual changes in ocean transport through Drake Passage are forced by variability in the Southern Annular Mode (SAM). This evidence is derived from two decades (1980s and 1990s) of subsurface pressure measurements from the tide gauge at Faraday station (western Antarctic Peninsula), combined with the output of an ocean general circulation model. In recent decades, the SAM has moved toward a higher‐index state (stronger circumpolar winds); this trend is not simply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 24 publications
12
124
1
1
Order By: Relevance
“…This suggests that the result may be model dependent, and further work is needed to understand the underlying mechanisms. These subpolar westerlies are an important driver of the ACC and DPT (Meredith et al 2004). A strengthening and poleward shift of the mid-latitude storm track is a robust response of GCMs forced by increasing GHGs (Yin et al 2005).…”
Section: Aerosol-induced Change (%) Ghg-only Change (%)mentioning
confidence: 99%
“…This suggests that the result may be model dependent, and further work is needed to understand the underlying mechanisms. These subpolar westerlies are an important driver of the ACC and DPT (Meredith et al 2004). A strengthening and poleward shift of the mid-latitude storm track is a robust response of GCMs forced by increasing GHGs (Yin et al 2005).…”
Section: Aerosol-induced Change (%) Ghg-only Change (%)mentioning
confidence: 99%
“…[8] It has been demonstrated that the BPR at the south side of Drake Passage (SD2; Figure 1) yields a reliable index of the oceanic transport through Drake Passage [Meredith et al, 1996[Meredith et al, , 2004; it has the added benefit of providing an almost continuous record, such that the 30-70-day filtered time series runs from 24 March 1990 to 29…”
Section: Antarctic Stationsmentioning
confidence: 99%
“…[2] Analysis of tide gauge and bottom pressure recorder (BPR) data has shown that oceanic subsurface pressure (SSP; sea level corrected for the ''inverse barometer effect'') and bottom pressure vary coherently around Antarctica on timescales from intraseasonal to interannual, coincident with changes in the oceanic circumpolar transport [Aoki, 2002;Hughes et al, 2003;Meredith et al, 2004]. Surface westerly (easterly) wind anomalies around the Southern Ocean close to Antarctica accelerate (decelerate) the oceanic circumpolar transport, associated with a fall (rise) in SSP and bottom pressure at the edge of the continent itself.…”
Section: Introductionmentioning
confidence: 99%
“…Because dense waters tend to be formed in relatively small geographic locations over the continental shelf, they are likely to be susceptible to changes in forcing associated with both natural and anthropogenic climate change. Understanding this potential variability is a significant challenge for climate modeling [Meijers, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Dense water export from the Weddell Gyre to the Scotia Sea and ACC has received significant attention in recent years [e.g., Meredith et al, 2004;Garabato et al, 2002;Meredith et al, 2011;Palmer et al, 2012]. The exact pathway of dense waters from the gyre to the ACC is heavily influenced by the presence of intervening topography, most notably the South Scotia Ridge running eastward from the tip of the Antarctic Peninsula ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%